Managing project task time uncertainty with probabilistic time buffers. (1st January 2011) - Bregman, Robert L.
Large-scale projects often include numerous tasks with uncertain durations. This results in complex probabilistic project networks that are difficult to manage because there are no well-defined critical paths. Since the joint probability of successfully completing all paths in these project networks before pre-defined due dates can be very low, it is beneficial to position time buffers to help ensure the completion of subtasks and the overall project. Unfortunately, because the number of potential buffer locations is large and the benefits of each involve numerous complex probabilistic interactions with other tasks and buffers, the best solution is difficult to determine. In addition, the best plans are likely to change over time as uncertain outcomes are realised and new information about future tasks is introduced. In response to this problem, this research introduces and tests a new approach that can be used to position (and reposition) time buffers at each project review.